"Police Sexual Violence: A Study of Policewomen as Victims". (March 2023) - Sands, Angela; Westerman, Laurel; Prochnau, Jenna; Blankenau, Henry
Police sexual violence (PSV) is an understudied but critically important topic in police research. This paper uncovers and examines an extremely hidden form of PSV: sexual assaults of female police officers by male police officers. Our qualitative analysis reveals how male police officers of widely varying ranks and years of experience sexually assault female police officers. Victims reported that the number of male police officers who sexually assault female police officers is small; however, victims reported that these officers are often serial offenders who also assault professional staff and citizens. Victims identified available investigative processes and reporting protocols, but they were afraid to report incidents due to concerns about potential retaliation from administrators and co-workers, limited career advancement or termination, being negatively viewed by co-workers, and simply not being believed. Victims believed that certain hypermasculine aspects of their agency and profession's culture allowed acts of PSV to happen, go unreported, and re-occur. We make several recommendations for how police administrators can address and prevent PSV in their agencies.